Unveiling the Local Atomic Arrangements in the Shear Band Regions of Metallic Glass - Mu, Xiaoke (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2021 The Authors. Advanced Materials published by Wiley-VCH GmbH.